2016
DOI: 10.1016/j.ynstr.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Social defeat stress induces depression-like behavior and alters spine morphology in the hippocampus of adolescent male C57BL/6 mice

Abstract: Social stress, including bullying during adolescence, is a risk factor for common psychopathologies such as depression. To investigate the neural mechanisms associated with juvenile social stress-induced mood-related endophenotypes, we examined the behavioral, morphological, and biochemical effects of the social defeat stress model of depression on hippocampal dendritic spines within the CA1 stratum radiatum. Adolescent (postnatal day 35) male C57BL/6 mice were subjected to defeat episodes for 10 consecutive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
70
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 99 publications
3
70
0
3
Order By: Relevance
“…During youth in rats (PD21–PD35), there is little information about the stress effect on synaptic communication, especially on dendritic spine density and dendritic arbor in neurons of limbic regions. Reports from our group and other groups have shown that prenatal and postnatal stress in the rat affects the dendritic tree and dendritic spine density in limbic regions (Ambeskovic et al, ; Gutiérrez‐Rojas et al, ; Íñiguez et al, ; Markham et al, ; Martínez‐Téllez et al, ; Monroy et al, ; Muhammad & Kolb, ; Muhammad et al, ; Suenaga et al, ). For example, prenatal stress in pregnant rats caused by 2‐hrs daily movement restraining from gestational day 11 until delivery caused a significant reduction in dendritic spine density in the CA1 and CA3 region of the hippocampus and nucleus accumbens (NAcc) in the offspring rats at postpubertal age (Martínez‐Téllez et al, ).…”
Section: Introductionmentioning
confidence: 89%
“…During youth in rats (PD21–PD35), there is little information about the stress effect on synaptic communication, especially on dendritic spine density and dendritic arbor in neurons of limbic regions. Reports from our group and other groups have shown that prenatal and postnatal stress in the rat affects the dendritic tree and dendritic spine density in limbic regions (Ambeskovic et al, ; Gutiérrez‐Rojas et al, ; Íñiguez et al, ; Markham et al, ; Martínez‐Téllez et al, ; Monroy et al, ; Muhammad & Kolb, ; Muhammad et al, ; Suenaga et al, ). For example, prenatal stress in pregnant rats caused by 2‐hrs daily movement restraining from gestational day 11 until delivery caused a significant reduction in dendritic spine density in the CA1 and CA3 region of the hippocampus and nucleus accumbens (NAcc) in the offspring rats at postpubertal age (Martínez‐Téllez et al, ).…”
Section: Introductionmentioning
confidence: 89%
“…The test induces a robust stress response (9), and the time animals spend immobile relative to the time they spend engaging in escape actions is interpreted as an indicator of their behavioral response to the uncontrollable stressor (7). Critically, prior exposure to stress diminishes behavioral responses during the TST (10). Thus, the TST assays an animal’s behavioral adaptation in response to prior stress exposure, and the test in and of itself induces a strong stress response.…”
Section: Introductionmentioning
confidence: 99%
“…In the current studies, a new three‐dimensional analysis of dendritic spines is combined with immunohistochemical staining allowing for colocalization of selected synaptic markers within various spine shapes. Our recent publication using this technique identifies rapid changes within particular spine shapes and changes in synaptic protein markers within these spines after stress and OP memory consolidation (Iniguez et al, ; Sebastian et al, ). Thus, this powerful technique can be utilized to understand E 2 's role in promoting spinogenesis and the synaptic markers within these spines.…”
mentioning
confidence: 99%
“…Animals were anesthetized and perfused either 30 or 120 min following E 2 or vehicle treatment as previously reported (Jacome et al, ). Brains were prepared for Golgi‐IHC staining and tertiary, apical spines in CA1 analyzed as previously reported (Iniguez et al, ; Sebastian et al, ). Data were analyzed using one‐way ANOVAs across treatments (vehicle, E 2 30 min, E 2 120 min) × various spine types (stubby, filapodia, long‐thin, mushroom) in combination with Tukey‐corrected t tests for post‐hoc analyses.…”
mentioning
confidence: 99%